A Catalogue of the genus-group theronia (hymenoptera:Inchneumonidae:pimplinae) from Sundaland - Amanda , T.P.O.; Yaakop , S; Idris , A.B (Pusat Sistematik Serangga ,UKM, 2011)
To date there are 14 species recorded from the genus-group theronia in Sundaland.A total of eight species from the genus theronia pseudozebra pseudozebra Gupta, theronia maskeliyae schmiedeknechti Krieger, Theronia flava gupta, theronia lucida cameron, theronia nigrivertex gupta, theronia clathrata malayensis gupta, theronia clathrata javensis gupta)with three species only found in java. One species from the genus parema that is parema nigrobalteata callida tosquinet and three species from the genus nomosphecia(nomosphecia zebroides zebroides Krieger, nomosphecia pyramida pyramida gupta, nomosphecia scutellata scutellata gupta) were recorded.Genus Augerella and Epitheronia each has one species, Augerella orientalis borneensis Gupta and Epitheronia tomeus Gupta,respectively.